Politik Hukum Berkeadaban Perspektif Filsafat Islam - Yogi Prasetyo (ARISTO, 2017)
This is the result of research that aims to explain the legal and political civilization civilized in Isla philosophical perspective. With literature study method and the philosophical approach of the data collected, verified and analyzed. The results showed that as the core of the Islamic civilization which can affect all aspects of human life and therefore civilization should become a legal political concept in accordance with Islamic values that have alignments to the virtues of the world of human life and the hereafter. Political law as a legal way to achieve legal establishment have made many disalahgunkan for maneuvering behind the legality of the law. The necessity to fix the legal politics only interest-oriented materialistic secular with Islamic philosophy, as with the values of Islam that comes from God as the highest authority over all can be transformed into a real life human being, so that the safety and happiness of the world and the hereafter can achieved.